CRISPR-Cas9 correction of OPA1 c.1334G>A: p.R445H restores mitochondrial homeostasis in dominant optic atrophy patient-derived iPSCs - Paul E. Sladen; Pedro R.L. Perdigão; Grace Salsbury; Tatiana Novoselova; Jacqueline van der Spuy; J. Paul Chapple; Patrick Yu-; Michael E. Cheetham (Elsevier, 2021)
Autosomal dominant optic atrophy (DOA) is the most common inherited optic neuropathy in the United Kingdom. DOA has an insidious onset in early childhood, typically presenting with bilateral, central visual loss caused by the preferential loss of retinal ganglion cells. 60%-70% of genetically confirmed DOA cases are associated with variants in OPA1, a ubiquitously expressed GTPase that regulates mitochondrial homeostasis through coordination of inner membrane fusion, maintenance of cristae structure, and regulation of bioenergetic output. Whether genetic correction of OPA1 pathogenic variants can alleviate disease-associated phenotypes remains unknown. Here, we demonstrate generation of patient-derived OPA1 c.1334G>A: p.R445H mutant induced pluripotent stem cells (iPSCs), followed by correction of OPA1 through CRISPR-Cas9-guided homology-directed repair (HDR) and evaluate the effect of OPA1 correction on mitochondrial homeostasis. CRISPR-Cas9 gene editing demonstrated an efficient method of OPA1 correction, with successful gene correction in 57% of isolated iPSCs. Correction of OPA1 restored mitochondrial homeostasis, re-establishing the mitochondrial network and basal respiration and ATP production levels. In addition, correction of OPA1 re-established the levels of wild-type (WT) mitochondrial DNA (mtDNA) and reduced susceptibility to apoptotic stimuli. These data demonstrate that nuclear gene correction can restore mitochondrial homeostasis and improve mtDNA integrity in DOA patient-derived cells carrying an OPA1 variant.